2010
DOI: 10.1007/s00428-010-0942-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of a p73 exon 2 GC/AT polymorphism with colorectal cancer risk and survival in Tunisian patients

Abstract: We examined the association of one linked GC/AT polymorphism at p73 with the risk of colorectal cancer. In the present study, we investigated whether this polymorphism was related to the risk of colorectal cancer, and whether there were relationships between the polymorphism and LOH, protein expression or clinicopathological variables. The p73 genotypes were determined by PCR-restriction fragment length polymorphism in 150 Tunisians patients with colorectal cancer and in 204 healthy control subjects. Immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Other studies have also explored the contribution of epigenetic changes to colorectal cancer carcinogenesis in Africa ( 278 , 282 285 ). For example, the methylation of UCH1 and p14ARF genes were reported to drive colorectal cancer in the presence of TP53 mutation in Tunisia ( 282 , 283 , 286 , 287 ). Other studies on the North African populations reported the influence of polymorphisms in telomere and mitochondrial D-loop region on the clinicopathological characteristics of the colorectal cancers among their patients ( 288 , 289 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have also explored the contribution of epigenetic changes to colorectal cancer carcinogenesis in Africa ( 278 , 282 285 ). For example, the methylation of UCH1 and p14ARF genes were reported to drive colorectal cancer in the presence of TP53 mutation in Tunisia ( 282 , 283 , 286 , 287 ). Other studies on the North African populations reported the influence of polymorphisms in telomere and mitochondrial D-loop region on the clinicopathological characteristics of the colorectal cancers among their patients ( 288 , 289 ).…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of these studies were showed in Table 1. Among these publications, there are 6 concerned about cervical cancer [17,34,40,50–52], 5 about lung cancer [16,29,33,35,38], 4 about colorectal cancer [28,37,46,47], 4 about esophageal cancer [14,27,28,39], 4 about gastric cancer [28,39,43,48], 3 about breast cancer [15,26,30], 3 about squamous cell carcinoma of the head and neck [32,41,45], as well as other 7 publications focus on Endometrial cancer [36], lymphoma [31], melanoma [42], nasopharyngeal carcinoma [53], neuroblastoma [25], ovarian cancer [44] and prostate cancer [49], respectively. As to the ethnicity, 14 studies were performed in Caucasians, while the other 22 studies were managed in Asian population.…”
Section: Resultsmentioning
confidence: 99%
“…However, another study failed to observe any significant association between the TP73 GC/AT variant genotype and allele distribution and clinical parameters of CRC. 30,35,42,44,57 Some previous studies identified the AC/GT genotype of G4C14-A4T14 as a significant risk factor for GCs, although other studies found no such association. 31,36,40,67,70 Decreased expression of p73 mRNA was identified in both inflammatory and noninflammatory BC cells compared with normal breast epithelial cells, indicating that this variant might increase the risk of BC by reducing the expression of p73.…”
Section: Discussionmentioning
confidence: 99%